ANÁLISE ECONÔMICA DO POLICULTIVO DE TILÁPIA-DO-NILO (Oreochromis niloticus) E CAMARÃO (Macrobrachium rosenbergii) EM AQUAPONIA INTEGRADO COM TECNOLOGIA DE BIOFLOCOS - Edilaine Fogaça (2021)
The great challenge for the improvement of intensive aquaculture production systems is based on the reduction in the use of water resources to renew and maintain its water quality and reduce effluent emissions. The application of BFT technology also favors the achievement of sustainable development goals, as it enables the activity to achieve results with greater productivity and less impact on the environment. The objective of the present work was to analyze economically the aquaponics system with polyculture of Nile tilapia and freshwater shrimp with and without the use of BFT Each treatment was composed by 6 modules, each module by two containers, one of 500L for allocating the plants and gravel; and another 1000 L to store fish and shrimp. The experimental period was 60 days, in which 276 Nile tilapia (Oreochromis niloticus) with an initial average weight of 438 g and 60 freshwater shrimp (Macrobrachium rosenbergii) with an initial average weight of 10 g were used. The following surveys were carried out among the cost system classifications: acquisition of animals and vegetable seedlings, labor, water quality control (BFT maintenance), nutrition, health, system maintenance and energy. The following economic values were generated: revenues, total operating cost (TOC), effective operating cost (COE), operating result, gross profit and share (%), making up the economic results statement (DRE).